Senam Kaki Sebagai Upaya Pencegahan Diabetic Foot pada Penderita Diabetes Mellitus Tipe 2 - Muhsinin, Siti Zuraida; Pujiningsih, Erniawati; Sulastien, Herni; Hadi, Sofian; Musniati, Musniati; Safitri, Saitun (PT.Mantaya Idea Batara, 2023)
Nurses are one of the health teams whose role is to help DM sufferers to prevent diabetic foot, one of which is by teaching DM sufferers to do foot exercises. Foot exercise is an activity or physical exercise performed by patients with diabetes mellitus by moving their feet. One of the goals is to help improve blood circulation in the legs, to prevent diabetic ulcer. Community service activities with the theme